Phytochemical sreening, proximate analysis and mineral composition of some leafy vegetables consumed in Nigeria - Idoko, Owoicho; Emmanuel, Stella; Aguzue, Ooyinye; Fausat, Akanji; Osuagwu, Ifeanyi; Asuquo, Thomas (International Journal of Advanced Chemistry, 2014)
Phytochemical screening, proximate analysis and mineral composition of nine leafy vegetables; Teifaria occidentalis, Veronia amygdalina, Ocinum gratissimum, Corchorus olitorius, Piper guineese, Amaranthus hybridus Talinum triangulare, Gnetum africanum and Murraya koenigii was carried out using standard methods. The proximate analysis results showed that the moisture, ash, crude lipid, crude fibre, crude protein and carbohydrate ranged as followed; 10.20 to 15.17%, 6.65 to 28.33%, 1.44 to 11.29%, 0.52 to 2.33% 2.24 to 35.21% and 22.66 to 62.80% respectively. The mineral composition results showed that on the average, highest concentration of calcium was recorded in the range of 838 to 1258mg/100g, while Cr was found to be the least with concentration range of 0.19 to 0.48mg/100g. Cd was absent in all the samples. The phytochemical screening results also showed the presence of tannin, alkaloids and carbohydrate in all the leafy vegetables. The result of this study indicates that the leafy vegetables could be a good supplement for some the nutrients and elements analyzed. Keywords: Leafy Vegetables, Mineral Composition, Phytochemicals, Proximate Analysis.